PENGARUH SELEBRITI ENDORSE (RAISA ADRIANA) TERHADAP MINAT BELI KONSUMEN PRODUK ESKRIM MAGNUM PADA MAHASISWA FAKULTAS EKONOMI BISNIS UNIVERSITAS ISLAM MALANG - Ahmad Busthami; Nur Hajati; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2020)
Abstract This study aims to examine the influence of celebrities who support consumer buying interest in Magnum ice cream products in students of the Faculty of Business Economics, University of Isalam Malang. The population in the study was 250, and a sample of 71 respondents was taken based on the Slovin formula. Technique data by distributing questionnaires. While the data analysis used the validity and reliability test, normality test, simple linear regression test and T test. The results showed that the validity test was declared valid with a calculated r value greater than r table, namely 0.23 and the reliability of the test was declared reliable with a Cronbach alpha value of more than 0.6. Then the normality test obtained a significance value of 0.833 which is greater than 0.05, so it is normally distributed. The simple linear regression test results of the regression equation Y = 1.371 + 0.615X show that the celebrity endors variable (X) increases, it will also cause an increase in the consumer interest variable (Y). whereas in the test, the t count value of 5.322 is greater than t table 1.667 and the sig value of 0.000 is less than 0.005, thus variable X has a positive and significant effect on variable Y.Keywords: Product Quality, Celebrity Endorse, Purchase Interest.